(3QSGdI aj GdCTQGa GdcjdGfjjf GdMehjjf GdbGWfjf HGdgfOs - (3GdQGeahQj , CMeO Hf Ydj GdgfOj,J (B1313 (3g` s
(3ChdgG (B:s
(3CeG HYO bO CNHQfi CMO ef Hfi CYeGei GdeSei GdSjO GdTQja JLed MSjf TGg HCf MVQI CHhESMGb EHQGgje GdcjdGfj GdMehi s
(3BNQgG (B:s
(3gPG eG habJ Edi ef ChdGO GdSjO GdTQja TgGH GdOjf CMeO GdMehi s
(3GdfSNI HgG MhGTs
(3gfGc Tc aj Cf eDda GdeNWhW gh fGSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B183 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B320s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B197 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs